MO175TROPONIN CUT-OFFS FOR ACUTE MYOCARDIAL INFARCTION IN PATIENTS WITH IMPAIRED RENAL FUNCTION - A SYSTEMATIC REVIEW AND META-ANALYSIS. (29th May 2021) - Kampmann, Jan; Granhøj, Jeff; Brandt Kristensen, Frans; Pedersen, Andreas; Backer Mogensen, Christian; Heaf, James G; Mickley, Hans
Abstract: Background and Aims: Background: Identifying acute myocardial infarction in patients with renal disease is notoriously difficult due to atypical presentation and chronically elevated troponin. Aim: To generate an optimized troponin cut-off value for patients with impaired renal function and acute myocardial infarction via meta-analysis. Method: Two investigators screened 2, 580 publications from Medline, Embase, Pubmed, Web of Science and Cochrane library. Only studies that investigated alternative cut-offs according to renal impairment were included. 15 articles fulfilled the inclusion criteria and results were included in a meta-analysis. Study characteristics and cut-off values were extracted. Study quality and risk of bias were assessed by using QUADAS-2 score. Six studies were included in the meta-analysis. To calculate the optimal cut off value in accordance to AUC for troponin T and troponin I in patients with renal impairment a bivariat mixed effect model on the sensitivity and specificity transformed by way of the inverse probit function similar to the model implemented in the R-package diagmeta was employed. Results: Review: There was a considerable diversity in study design, study population and endpoint definition. The cut-off value for patients on peritoneal dialyses was twice as high (144 ng/L) when compared to patients on hemodialysis (75 ng/l). Asian studies suggested a substantially higher troponin cut-off when compared to European and American studies. The risk of bias was low in the analyzed studies, yet several studies were considered to have a low applicability. Meta-analysis: Cut-off value for troponin T in patients not in dialysis with eGFR <60 ml/min/1.73m2, a troponin T value of 47.89 ng (23.95; 71.83) was found. In patients on dialysis a troponin T value of 239.75 ng/l ( 69.27 ; 410.23) was demonstrated. The 99 th percentile of the upper reference limit for troponin T was 14 ng/l. Cut-off value for troponin I: In patients not in dialysis with eGFR < 60 ml/min/1.73m² a troponin I value of 42.45 ng/l ( 33.83 ; 51.08 ) was demonstrated. The 99 th percentile of the upper reference limit for troponin I ranged from 9-42 ng/l depending on the assays used. Troponin I cut-off for patients in dialysis could not be calculated due to limited data. Conclusion: The new cut-off values could help to identify patients whose troponin suggests acute myocardial infarction rather than renal function related troponin elevation. The meta-analysis is based on only six studies in total. Further subdivision according to eGFR would be desirable in order to optimize troponin cut-off values especially for dialysis patients. A differentiation on troponin cut-offs for HD and PD patients may yield further benefits. Asian studies suggested a substantially higher troponin cut-off when compared to European and American studies. The factors behind these findings may be worth investigating.